UPAYA PENINGKATAN MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI MELALUI PENERAPAN MODEL PEMBELAJARAN STAD - SRIDEVI NURHAERANI ACHMAD,; TUTI SUPATMININGSIH,; INANNA,; MUHAMMAD HASAN,; RAHMATULLAH, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study aims to increase the motivation and learning outcomes of students in economic subjects using the Student Team Achievement Division (STAD) learning Model. The research method uses this type of classroom action research with data collection methods trhough observation, ability tests and documentation during the second cycle. The subject of the research were 31 students of class X IPS 4 at SMAN 4 Makassar. The result of this study indicate that the motivation and learning putcomes of students during the learning process using the STAD learning model have increased. This increase was seen from the first cycle post-test seen from 31 students, there were 11 students who had not completed and 20 others got complete scores with the percentage of completeness of 64,51% and the category of the average score of student as “good”. Then in the second cycle there were 28 students got complete score with a compeleteness percentage of 90,32% and score category of 13 students who were “very good” and others in the good “category”.